I don't know what you mean by "the idea that a - b = a + (b)"
That makes no sense. The problem may be with your teacher.
IF b is negative,
a - b = a + |b|
but that is not true if b is positive.
In any case,
a. -12 - (-6) = -12 + 6 = -6
b. -7 -4 = -11
c. 11 -(-8) = 11 + 8 = 19
Find the difference by using the idea that a - b = a + (b):
a. -12 - (-6)
b. - 7 - 4
c. 11 - (-8)
Thank you, I do not understand.
2 answers
Mary Lee probably has a typo and meant to say:
a - b = a + (-b)
If not, and your notes contain the statement the way you typed it, then you have to correct it in your notes.
I will do the first one:
a. -12 - (-6)
= -12 + (+6)
= -6
Do the others the same way
a - b = a + (-b)
If not, and your notes contain the statement the way you typed it, then you have to correct it in your notes.
I will do the first one:
a. -12 - (-6)
= -12 + (+6)
= -6
Do the others the same way